Implementation of STAD Learning Model Assisted by a Snakes and Ladders Game to Improve Learning Activeness for Students - Musfirah, Musfirah; Israwaty, Ila; Balulu, Iqrajatni Kireyratugi (PT. Riset Press International, 2026)
The problem in this study is the low learning activeness of class IV students. The problem in this study is how the Implementation of Student Team Achievement Division (STAD) Cooperative Learning Model Assisted by Snakes and Ladders Game to increase student learning activeness in IPAS learning in class IV UPTD SD Negeri 7 Benteng. This research is included in the type of class action research (PTK) which aims to determine the process and results of the application of the Student Team Achievement Division (STAD) Cooperative Learning Model Assisted by Snakes and Ladders Game to increase student learning activeness in IPAS learning in class IV with data collection techniques in the form of observation and documentation. The data analysis technique used is reducing data, presenting data, and drawing conclusions. The subjects of this study amounted to 17, namely 1 fourth grade teacher and 16 students. In cycle I, the results of research on the learning process were in the qualification of sufficient (Enough) and student learning activeness is in the medium category. Cycle II research results in the learning process are in good qualifications (B) and student learning activeness is in the High category. The conclusion of this study is that the application of the Student Team Achievement Division (STAD) Cooperative Learning Model assisted by the Snakes and Ladders Game can improve the process and activeness of student learning in IPAS learning in class IV UPTD SD Negeri 7 Benteng.